A comprehensive comparison of tools for differential ChIP-seq analysis - Steinhauser, Sebastian; Kurzawa, Nils; Eils, Roland; Herrmann, Carl (Briefings in bioinformatics, 2016)
ChIP-seq has become a widely adopted genomic assay in recent years to determine binding sites for transcription factors or enrichments for specific histone modi